STUDY ON CLINICAL CHARACTERISTICS, CONE BEAM TOMOGRAPHY OF PATIENTS WITH TEMPOROMANDIBULAR DISORDERS AT CAN THO UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL IN 2021 – 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical characteristics of the TMJ images of patients withtemporomandibular disorders at the Hospital of Can Tho University of Medicine and Pharmacy in2021 - 2022.Methods: Patients with temporomandibular disorders were diagnosed according to McNeil (1997)criteria. The patient has one of three symptoms: Pain in the masticatory system, temporomandibularjoint, and/or perianal region, often aggravated by palpation or functional activity. Jaw deviationwhen opening mouth with or without joint crackling. Limited mouth opening (≤ 40 mm). Agree toparticipate in the study. Sampling method: Convenience sampling over 35 patients.Results: Temporomandibular dysfunction appeared more in the age group from 16 to 35 (mean28.54 ± 9.08). Women are more likely to get the disease than men, with a female/male ratio of4/ first. Temporomandibular disorders appear in many students, students, and intellectual workersdue to the impact of psychological stress factors. Clinical signs according to McNeil criteria: Painin the joint area when moving the jaw accounts for 100%, and Arthralgia accounted for 82.5%.Limited opening of the mouth accounted for 48.6%. Status of TDH joints on Cone Beam ComputedTomography (CBCT) film: Round shape is the majority, with a rate of 59.4%. The flat shape has 3/35patients (6.8%). The average size of the condyle in the T - S direction is 8.14mm; N - T dimension is18.27mm. The condyle position posteriorly accounted for the majority (65.7%).Conclusion: The temporomandibular joint disorder seems to be significantly associated withdepression, anxiety and stress, and the distribution of condylar position in the articular fossa has adifferent ratio between of the condyles in the study are round.
Keywords: Temporomandibular joint, condyle, Cone Beam Computed Tomography.